Analisis Penerapan Konsep Syari’ah Pada Hotel Hidayah Tebuireng Jombang (Tinjauan Fatwa DSN-MUI No : 108/DSN-MUI/X/2016) - Alfiina Rohmatil Aliyah; Andriani Andriani (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2023)
The number of shari'ah hotels or what can be called a type of business in the halal sector which is currently being developed is also found in Jombang Regency, East Java, the purpose of this study was to find out how the application of the shari'ah concept to Hidayah Hotels. This study uses a descriptive explorative methodology and is qualitative in nature. The technique used in this study was in-depth interviews with hotel managers Hidayah Tebuireng and hotel guests using observation and documentation models, as well as reviews from the Hidayah hotel website which are found on Google as public information. The findings of this study indicate that the Hidayah hotel in Jombang Regency follows the DSN MUI fatwa No. 108/DSN-MUI/X/2016 in implementing the DSN MUI fatwa.